Half diallel of F1 tomato hybrid and its double cross-compatibility - MUH FARID; MUHAMMAD FUAD ANSHORI; IFAYANTI RIDWAN; NOVATY ENY DUNGGA; IRNA ERMIYANTI (Society for Indonesian Biodiversity, 2022)
Abstract. Farid M, Anhsori MF, Ridwan I, Dungga NE, Ermiyanti I. 2022. Half diallel of F1 tomato hybrid and its double cross-compatibility. Biodiversitas 23: 1813-1821. Breeding program for improvement of tomato fruit can be done through diallelic crosses genetic combinations. Therefore, genetic evaluation is needed to meet the breeding objective. This process can be combined with crosses between F1 to produce high diversity. However, evaluating the crosses' compatibility is required to increase the effectiveness of the assembly process. This study aimedto assess the half-diallel crosses of F1 tomatoes in the field and determine the most compatible pair cross combinationsin forming double and three-way F1 populations. This study was carried out in the Experimental Farm of the Faculty of Agriculture, Hasanuddin University. The field evaluation was arranged ina randomized complete block design with ten genotypes, while the compatibility evaluationwas carried out using 6 F1 half diallel as the parents. The results showed that the Mawar and Chung varieties were better parents in the crossings. Furthermore, the results showed that F1 K/M (the best yield component), M/C (the best TDS and Lycopene traits), and BC/K (the genotype has good traits of yield component, TDS and Lycopene) were the best single F1 crosses that could be inherited to the F2 generation. In contrast, F1 K/M and F1 K/C crosses were the best male and female parents, respectively. The recommended double-crosses include K/C//BC/M, and BC/C//K/M, while for the F1 unbalanced three-way cross was K/C//K/M.